Функціональна специфіка категорії героїчного в українському епосі - Малинська, Н. (Народна творчість та етнографія, 2008)
In artistic thinking of each historically conscious people heroic spirit and heroic deeds had been making a track to a word during many centuries. Over these centuries important and significant events were comprehended and interpreted as heroic ones. Functional specification of heroic deeds in the Ukrainian epos is an important factor for understanding of peculiarities of the Ukrainians’ attitude. So the article by N. Malynska is dedicated to this issue.